Microwave Heat Treatment to Manufacture Foam Glass Gravel - Lucian Paunescu (Journal La Multiapp, 2021)
Abstract The paper aimed at the experimental manufacture of a foam glass gravel type by sintering at over 900 ºC a powder mixture composed of recycled glass waste (92%), sodium borate (6%), kaolin (0.3%), silicon carbide (1.7%) and water addition (12%). The originality of the work was the application of the unconventional technique of microwave heating through a predominantly direct heating procedure. The product foamed at 908 ºC had a very fine porous structure (pore size between 0.05-0.20 mm) and a compressive strength above the usual level of foam glass gravels (7.8 MPa). The apparent density of 0.28 g/cm3 corresponding to a bulk density of 0.20 g/cm3 and the thermal conductivity of 0.075 W/m·K ensures the thermal insulating character of the material required for use in the specific field of applications of foam glass gravel. The manufacturing process had an excellent energy efficiency, the specific energy consumption decreasing up to 0.70 kWh/kg.